Arthur Woods papers - Woods, Arthur, 1870-1942.
Diary, correspondence, reports, notes, scrapbooks, clippings, and photographs pertaining chiefly to Woods's service as New York City police commissioner, colonel in the U.S. War Dept. Division of Military Aeronautics, and assistant to the U.S. secretary of war. Also documents Woods's work with John D. Rockefeller during the 1920s and 1930s. Subjects include Woods's youth in Boston, Mass.; airplane production and maintenance, pilot training, and military preparedness during World War I; vocational rehabilitation for servicemen and unemployment following World War I; and restoration of Williamsburg, Va.
Microfilm edition available
Microfilm edition produced from originals in the Manuscript Division.
U.S. Army officer and New York city police commissioner.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Rockefeller, John D., -- Jr. -- 1874-1960.; United States. -- War Department; United States. -- War Department. -- Division of Military Aeronautics; Airplanes, Military -- United States -- Maintenance and repair; Airplanes, Military -- Piloting -- United States; Airplanes, Military -- United States -- Design and construction; Military readiness; Police administration -- New York (State) -- New York; Unemployment -- United States; Vocational rehabilitation -- United States; World War, 1914-1918.; Boston (Mass.) -- Social life and customs; United States -- Defenses; Williamsburg (Va.) -- History; Army officers; Police commissioners